Patterns of pulmonary dysfunction in asbestos workers: a cross-sectional study - Abejie, Belayneh A (BioMed Central, 2010)
BACKGROUND: Restrictive patterns of pulmonary function abnormalities associated with asbestos exposure are well described. Studies are less consistent, however, regarding the association of asbestos inhalation with airway dysfunction and obstructive impairment. METHODS: We compared pulmonary function test results between 277 chrysotile exposed workers (22% non-smokers) and 177 unexposed controls (50.3% non-smokers). Information on exposure and smoking were collected using a standardized questionnaire. Standardized spirometric and DCLO Measurement methods were utilized. CXRs were read based on ILO pneumoconiosis guidelines. RESULTS: Asbestos exposed subjects had significantly reduced FVC, FEV1, FEV1/FVC and DLCO. Restricting the analysis to non-smokers, asbestos workers still had about 3% lower FEV1/FVC ratio than controls, but this difference did not reach statistical significance. Among exposed workers, the presence of radiographic evidence of asbestosis further lowered FVC and DLCO but not FEV1/FVC compared to asbestos exposure without radiographic asbestosis. Additionally, smoking asbestos workers had significantly lower DLCO compared to non-smoking workers. CONCLUSION: Asbestos exposure, especially when radiographic evidence of interstitial fibrosis from asbestosis is present, leads to significant decreases in FVC, FEV1 and the DLCO. However, asbestos exposure alone is not significantly associated with a reduction of the FEV1/FVC. Smoking-asbestos workers had significantly lower DLCO than their non-smoking counterparts. Whether asbestos interacts with smoking additively or synergistically on DLCO needs further investigation. Similarly, further studies are needed to assess the progression and clinical significance of asbestos induced airway dysfunction.